Strategies for tobacco control in India: a systematic review. - Ailsa J McKay; Raju K K Patel; Azeem Majeed (PLoS ONE, 2015)
BACKGROUND:Tobacco control needs in India are large and complex. Evaluation of outcomes to date has been limited. AIM:To review the extent of tobacco control measures, and the outcomes of associated trialled interventions, in India. METHODS:Information was identified via database searches, journal hand-searches, reference and citation searching, and contact with experts. Studies of any population resident in India were included. Studies where outcomes were not yet available, not directly related to tobacco use, or not specific to India, were excluded. Pre-tested proformas were used for data extraction and quality assessment. Studies with reliability concerns were excluded from some aspects of analysis. The Framework Convention on Tobacco Control (FCTC) was use as a framework for synthesis. Heterogeneity limited meta-analysis options. Synthesis was therefore predominantly narrative. RESULTS:Additional to the Global Tobacco Surveillance System data, 80 studies were identified, 45 without reliability concerns. Most related to education (FCTC Article 12) and tobacco-use cessation (Article 14). They indicated widespread understanding of tobacco-related harm, but less knowledge about specific consequences of use. Healthcare professionals reported low confidence in cessation assistance, in keeping with low levels of training. Training for schoolteachers also appeared suboptimal. Educational and cessation assistance interventions demonstrated positive impact on tobacco use. Studies relating to smoke-free policies (Article 8), tobacco advertisements and availability (Articles 13 and 16) indicated increasingly widespread smoke-free policies, but persistence of high levels of SHS exposure, tobacco promotions and availability-including to minors. Data relating to taxation/pricing and packaging (Articles 6 and 11) were limited. We did not identify any studies of product regulation, alternative employment strategies, or illicit trade (Articles 9, 10, 15 and 17). CONCLUSIONS:Tobacco-use outcomes could be improved by school/community-based and adult education interventions, and cessation assistance, facilitated by training for health professionals and schoolteachers. Additional tobacco control measures should be assessed.